Quaternary seismic facies of the South Yellow Sea shelf: depositional processes influenced by sea‐level change and tectonic controls. (17th May 2016) - Li, X. S.; Zhao, Y. X.; Feng, Z. B.; Liu, C. G.; Xie, Q. H.; Zhou, Q. J.
Abstract: The South Yellow Sea (SYS) is a semi‐closed epicontinental sea, where voluminous material input and regional tectonic subsidence facilitate preservation of depositional strata, making it an ideal place for studying the regional responses to global sea‐level changes during the Quaternary. Based on high‐resolution single‐channel seismic data, we conducted a detailed study of the SYS shelf in terms of its stratigraphic architecture and seismic facies. In combination with borehole data, we analysed the depositional processes of the SYS shelf since the Quaternary. A minimum of 14 seismic sequences were identified on the seismic profiles, which primarily show four typical seismic reflection facies: progradational reflection facies, parallel reflection facies, chaotic reflection facies and incised valley facies, with the former two seismic facies usually alternating with the latter two vertically. Borehole and seismic data revealed that the SYS shelf has been basically controlled by global sea‐level changes since the Quaternary, and three significant transgression events had occurred over the SYS shelf since the Middle Pleistocene ( ca . 730 ka BP–Present), taking place in the early Middle Pleistocene, the early Late Pleistocene and at the end of the Late Pleistocene–Holocene, respectively, with their products corresponding to seismic sequences U90, U50 and U10, respectively. Seismic data showed that, in a previous division of the main boundaries for holes EY02‐2, NHH01 and QC2, the Holocene and the Upper Pleistocene bottom boundaries are concordant, while the Middle Pleistocene bottom boundary is discordant, and our study indicated that the division scheme for the Middle Pleistocene bottom boundary related to holes EY02‐2 and NHH01 is more reasonable. The turning point of variation in the depositional environment of the SYS is at the end of the Middle Pleistocene, before which global sea‐level change and tectonic subsidence controlled the shelf deposition. The shelf was inclined westwards and the tectonic topography of the southern margin of the shelf‐forced seawater to invade via passages during sea‐level rise. This resulted in a limited stratigraphic distribution formed by short‐duration transgression events with low‐amplitude sea‐level rise; thereafter, the shelf deposition was predominated by global sea‐level and rivers, and the shelf sediments were mainly derived from mainland China on the west of the shelf and were primarily accumulated on the middle and western parts of the shelf. Copyright © 2016 John Wiley & Sons, Ltd.